Răspuns :
Răspuns:
a) [tex]1 - \frac{4}{7} = \frac{7}{7} - \frac{4}{7} = \frac{7 - 4}{7} = \frac{3}{7}[/tex]
b) [tex]1 - \frac{7}{8} = \frac{8}{8} - \frac{7}{8} = \frac{8 - 7}{8} = \frac{1}{8}[/tex]
c) [tex]1 - \frac{2}{9} = \frac{9}{9} - \frac{2}{9} = \frac{9 - 2}{9} = \frac{7}{9}[/tex]
d) [tex]1 - \frac{3}{4} = \frac{4}{4} - \frac{3}{4} = \frac{4 - 3}{4} = \frac{1}{4}[/tex]
e) [tex]3 - \frac{1}{2} = \frac{6}{2} - \frac{1}{2} = \frac{6 - 1}{2} = \frac{5}{2} = 2 + \frac{1}{2}[/tex]
f) [tex]2 - \frac{3}{4} = \frac{8}{4} - \frac{3}{4} = \frac{8 - 3}{4} = \frac{5}{4} = 1 + \frac{1}{4}[/tex]
g) [tex]1 - \frac{4}{15} = \frac{15}{15} - \frac{4}{15} = \frac{15 - 4}{15} = \frac{11}{15}[/tex]
h) [tex]1 - \frac{3}{7} = \frac{7}{7} - \frac{3}{7} = \frac{7 - 3}{7} = \frac{4}{7}[/tex]
Explicație pas cu pas: